2000
DOI: 10.1093/carcin/21.12.2293
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation of defective mitotic checkpoint with aberrantly reduced expression of MAD2 protein in nasopharyngeal carcinoma cells

Abstract: Nasopharyngeal carcinoma (NPC) occurs with a high incidence in many countries in south-eastern Asia. Chromosomal abnormalities have been commonly found in NPC, but the underlying mechanism is not well understood. We determined mitotic indices, the staining pattern of nuclear DNA and cell cycle profiles of NPC cells in response to treatment with microtubule-disrupting agents, and found that the mitotic checkpoint was defective in two out of five (40%) of the tested NPC cell lines. We also observed that an aberr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 23 publications
3
66
0
Order By: Relevance
“…In summary, we have shown that down-regulation of MAD2, a feature common to many tumour cell lineages (Takahashi et al, 1999;Wang et al, 2000Wang et al, , 2002Fung et al, 2007) induces cellular senescence in up to a third of the cell population. Due to the fact that paclitaxel targets actively dividing cells, these cells will evade cytotoxic-induced death.…”
Section: Discussionmentioning
confidence: 53%
“…In summary, we have shown that down-regulation of MAD2, a feature common to many tumour cell lineages (Takahashi et al, 1999;Wang et al, 2000Wang et al, , 2002Fung et al, 2007) induces cellular senescence in up to a third of the cell population. Due to the fact that paclitaxel targets actively dividing cells, these cells will evade cytotoxic-induced death.…”
Section: Discussionmentioning
confidence: 53%
“…FAT10 has been reported to bind noncovalently to MAD2 (Liu et al, 1999), a protein necessary for maintaining spindle integrity during mitosis (Shah and Cleveland, 2000), suggesting that it may play a role in regulating genomic stability. Indeed, MAD2 dysregulation has been associated with chromosomal instability (Wang et al, 2000;Gemma et al, 2001) and has been shown to cause increased tumor incidence in mice (Michel et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…FAT10 has been shown to bind noncovalently to the human spindle assembly checkpoint protein, MAD2 (Liu et al, 1999), a protein responsible for maintaining spindle integrity during mitosis (Shah and Cleveland, 2000). The inhibition of MAD2 function has been associated with chromosomal instability, a characteristic of many cancers (Wang et al, 2000;Gemma et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…80 SAC involvement in tumorigenesis, however, is very complex and context-dependent. For instance, downregulation of SAC proteins such as Mad2 is also observed in certain liver, 81 ovarian, 82 nasopharyngeal, 83 and breast 84 cancer lines. Complete knockdown of Mad2 is embryonically lethal and results in severe aneuploidy and apoptosis in mice.…”
Section: Surviving With Surplus: Managing Supernumerary Centrosomes Bmentioning
confidence: 99%